2005
DOI: 10.1002/gps.1358
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic use in the elderly: shifting trends and increasing costs

Abstract: The modest increase in antipsychotic prevalence in the elderly over the last ten years has been associated with a substantial increase in cost, with a significant shift towards use of the atypical antipsychotics. As the atypical antipsychotics are increasingly used for patients with dementia, which is becoming more prevalent in the aging population, an understanding of the benefits of these medications must be balanced with a detailed understanding of the material and financial implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
40
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 24 publications
5
40
1
Order By: Relevance
“…3 In 2001, more than 70% of US atypical antipsychotic prescriptions were written for offlabel indications such as dementia, 4 and atypical antipsychotics accounted for 82% of antipsychotic prescriptions written for older patients in Canada in 2002. 5 Some pharmaceutical companies may have aided this growth by promoting the use of atypical antipsychotics for off-label purposes. 6 However, starting in 2002, worries began to arise about atypical antipsychotic safety including concerns about diabetes 7 and cerebrovascular events 8,9 (the latter emerging from randomized placebocontrolled trials of patients with dementia).…”
Section: Arch Gen Psychiatry 2011;68(2):190-197mentioning
confidence: 99%
“…3 In 2001, more than 70% of US atypical antipsychotic prescriptions were written for offlabel indications such as dementia, 4 and atypical antipsychotics accounted for 82% of antipsychotic prescriptions written for older patients in Canada in 2002. 5 Some pharmaceutical companies may have aided this growth by promoting the use of atypical antipsychotics for off-label purposes. 6 However, starting in 2002, worries began to arise about atypical antipsychotic safety including concerns about diabetes 7 and cerebrovascular events 8,9 (the latter emerging from randomized placebocontrolled trials of patients with dementia).…”
Section: Arch Gen Psychiatry 2011;68(2):190-197mentioning
confidence: 99%
“…A Canadian study found that the prevalence of antipsychotic use in older adults increased from 2.2% in 1993 to 3.0% at the end of 2002. In that study, atypical antipsychotics, which were unavailable in 1993, accounted for 82.5% of all antipsychotics dispensed in 2002 (8). Short-term randomized, controlled trials (RCTs) have studied the role of atypical antipsychotics in the management of behavioral and psychological symptoms of dementia (2,9).…”
mentioning
confidence: 99%
“…Since the introduction of atypical antipsychotics, in the 1990s, the use of and costs associated with these drugs have increased substantially. [1][2][3][4][5][6] This increase has been driven primarily by prescriber preference for atypical (or second-generation) antipsychotics, 1,2 higher costs of newer agents compared with typical (or first-generation) antipsychotics 1 and a widening range of on-and off-label uses. [3][4][5][7][8][9] The increase in the use of atypical antipsychotic medications has been particularly marked in older adults with dementia.…”
mentioning
confidence: 99%